Management Risiko sebagai Pemoderasi dalam Hubungan ESG Disclosure terhadap Kinerja Keuangan pada Industri Tambang 2021-2024 - Muhammad Islah Syafi’i; Sifah Fauziah; Nur Asty Dwi Febriyani Syam; Siti Nurul Izza Azhari; Nurfadhysa Nurfadhysa; Alia Rezki Amalia (AKUNTANSI 45, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on financial performance with risk management as a moderating variable in mining companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. Secondary data were obtained from annual and sustainability reports, selected using purposive sampling with disclosure standards based on GRI 2021 and ERM COSO. Financial performance was measured by ROA and ROE, while multiple regression analysis was employed. The results show that ESG disclosure has a significant positive effect on financial performance, and Enterprise Risk Management (ERM) strengthens this relationship despite some indication of autocorrelation. These findings support signaling and stakeholder theory, emphasizing that sustainability disclosure combined with integrated risk management not only enhances legitimacy but also provides tangible benefits for governance quality and financial performance in the Indonesian mining industry.